INDICATORS OF THE LEVEL OF SUBJECTIVE CONTROL IN MALE PATIENTS WITH MILD OR SEVERE PSORIASIS WITHOUT TAKING INTO ACCOUNT SOMATOTYPE AND WITH TAKING INTO ACCOUNT SOMATOTYPE - Serebrennikova, О.А.; О. Б. А-Р. Аль-Каралех,; Dzevulska, І.V.; Kryvonis, T.G.; Prolygina, I.V. (World of Medicine and Biology, 2022)
In men with mild or severe psoriasis, compared with healthy subjects without division into somatotypes, the level of subjective control showed a significant decrease in the value of interpersonal relationships and the ability to influence their own health. Significantly lower levels of general internality in patients with severe psoriasis were found in the distribution by body type in men of mesomorphic somatotype as well as the indicator of the level of subjective control in the field of failures, educational and interpersonal relationships in patients with mild and severe disease compared with the control group of a similar somatotype.
Keywords: psoriasis; severity; men; level of subjective control; body type